The Importance of Interdisciplinary Relations of Physics and Statics - Vackova, Martina; Kancirova, Maria; Kovacova, Lucia (Communications - Scientific letters of the University of Zilina, 2016)
The article will discuss the importance of respecting and applying the didactic principle of interdisciplinary relations in Physics and Statics taught at the University of Security Management in Kosice. The subjects Statics and Physics, which are based on natural principles, allow to get the necessary analytical and logical thinking for understanding other technical and science subjects. Application of the principle of interdisciplinary relations helps to increase efficiency and quality of the teaching process, motivates and activates students. The article describes the possibilities of using physical knowledge in the subject Statics.